2016
DOI: 10.1186/s12967-016-1056-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in tumor microenvironment: novel transporters and biomarkers

Abstract: Tumor microenvironment (TME) plays an integral part in the biology of cancer, participating in tumor initiation, progression, and response to therapy. Exosome is an important part of TME. Exosomes are small vesicles formed in vesicular bodies with a diameter of 30–100 nm and a classic “cup” or “dish” morphology. They can contain microRNAs, mRNAs, DNA fragments and proteins, which are shuttled from a donor cell to recipient cells. Exosomes secreted from tumor cells are called tumor-derived (TD) exosomes. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 64 publications
0
116
0
1
Order By: Relevance
“…Additionally, these results provide evidence that IGF1 may be a key factor in the promotion of EOC progression through TAMs, explaining its high expression in EOC. Finally, we propose that the mechanism of the upregulation of IGF1 in ID8 cells through TAMs may involve exosomes, which could transfer microRNAs, mRNAs, DNA fragments and proteins, particularly miRNA, from donor cells to recipient cells (42) or secrete cytokines, which also play an important role in the communication between different cells (43). However, these hypotheses need further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these results provide evidence that IGF1 may be a key factor in the promotion of EOC progression through TAMs, explaining its high expression in EOC. Finally, we propose that the mechanism of the upregulation of IGF1 in ID8 cells through TAMs may involve exosomes, which could transfer microRNAs, mRNAs, DNA fragments and proteins, particularly miRNA, from donor cells to recipient cells (42) or secrete cytokines, which also play an important role in the communication between different cells (43). However, these hypotheses need further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exosome cargo varies, depending on the health status of the tissue of origin, thus serving as biomarkers of specific tissue health status. This was first discovered in cancer studies, where it was shown that plasma levels of substances peculiar to cancer cells could serve as biomarkers of disease progression 5 . Since then, identifying the contents of exosomes from plasma has revealed molecular signatures of numerous pathologies, including heart failure and myocardial infarction.…”
Section: - How Do Cells Secrete? Conventional and Unconventional Secmentioning
confidence: 99%
“…Exosomes are small membrane-bound nanovesicles with the characteristic size of 30-120 nm in diameter [5]. Exosomes are generated from endosomal origins constitutively, released by various cells, and more frequently by tumor cells [6][7][8].…”
Section: Introductionmentioning
confidence: 99%